Nationwide Awareness Campaign and Call for Dental Screening for Hereditary Hemorrhagic Telangiectasia in Germany - Urban W. Geisthoff; Frank Hölzle; Boris A. Stuck; Joachim Jackowski; Catherine Hand Goetz; Christina Grabowski; Freya Droege (Hindawi Limited, 2023)
Objectives. Hereditary hemorrhagic telangiectasia (HHT) is a rare disorder encompassing facial and oral telangiectasias and visceral vascular malformations (VMs). Pulmonary VMs can lead to paradoxical embolism of thrombi or bacteria, e.g., due to dental procedures. Early detection can reduce morbidity and mortality and is recommended. However, diagnosis is often delayed for decades. Our study is assessing the feasibility and effect of a nationwide awareness campaign for early diagnosis of HHT addressing all dentists in Germany. Methods. In 2018, one article and two reminders about HHT were published in a nationwide awareness campaign. As a proxy for the effectiveness of the campaign, researchers measured the number of first-time inquiries from patients and physicians about HHT documented by the German HHT self-help group from September 2016 until September 2019. Results. A total of 411 first contacts with the German self-help group were documented, mainly via Internet platforms (Internet forum (n = 130) and Facebook® (n = 189)). For 9% of those patients (n = 36/411), the physician or dentist (physician: (n = 31/36, 86%; dentist: n = 5/36, 14%) informed patients about the disease HHT and the self-help group. Before publishing the first article about HHT, no dentist referred patients to the German self-help group; afterwards, 5 patients received information about HHT from their dentist and contacted the patient organization for the first time. After each publication in June, September, and December 2018, the number of new contacts increased. Contacts via phone and e-mail had the highest relative increase. Conclusions. The repeated call for dental screening for HHT in Germany led to increased awareness of this rare disease; more patients with possible HHT received information about the condition. The authors conclude that targeted campaigns may contribute to a shorter diagnostic latency resulting in increased quality of life and life expectancy in HHT. This trial is registered with CT03549949.